Green hub-and-spoke network design for aviation industry. (20th August 2019) - Parsa, Mostafa; Nookabadi, Ali Shahandeh; Flapper, Simme Douwe; Atan, Zümbül
Abstract: In response to the rapid growth of environmental problems related to air transportation including emissions and noise, aviation authorities and industries have implemented stricter environmental regulations and targets in the early 2000s to encourage airlines to become greener. Different emission mitigation measures to achieve these targets have been developed. This study introduces a new mitigation measure. In addition to minimizing the total cost of flow and establishing hubs, the measure aims at minimizing the greenhouse gas emissions, fuel consumption and noise in the design of airline hub-and-spoke network. We develop a multi-objective mixed integer-programming model and use several methodologies to determine the best design. Our computational results are based on the CAB data set for the domestic US aviation sector. For assessing the value of the new mitigation measure, we develop cumulative marginal abatement cost curves for reducing the projected annual CO 2 emissions from 2020 to 2050 for the domestic US air transportation. Our results indicate that using the new measure can cost-effectively decrease the projected cumulative (2020–2050) CO 2 emissions by more than 250 and 200 million tonnes relative to the classical model, which relies on minimizing the total cost of flow and opening hubs only. We conclude that the new measure not only provides a practical solution for the airlines facing high fuel cost, emission trading schemes or carbon tax systems but it can also play an important role in achieving sustainable and environmental-friendly targets.